2020
DOI: 10.1016/j.jid.2019.07.713
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-26 Expression Promotes T Helper Type 17- and T Helper Type 2-Associated Cytokine Production by Keratinocytes in Atopic Dermatitis

Abstract: Whereas atopic dermatitis (AD) is considered as a T helper 2 (Th2)-centered disease, IL-17eproducing Th (Th17) cells are also activated in AD lesional skin. However, the relationship between Th17 responses and Th2 responses in AD is still to be elucidated. Although Th17 cells are increased in AD skin, the expression and function of IL-26, which is also produced by Th17 cells, in AD are still unknown. In this report, we demonstrated that IL-26 mRNA expression levels were elevated in AD lesional skin compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
0
40
1
2
Order By: Relevance
“…Cluster 1 showed increased expression of KLF2 (Fig E11, C), a transcription factor involved in T cell homeostasis mediating quiescence and survival, that is present in naive as well as quiescent mature memory T cells, being downregulated upon T-cell receptor-mediated activation. 51 Thus, we conclude that cluster 1 represents quiescent memory T cells, while cluster 0 harbors activated memory T cells with effector functions mediated by active production of proinflammatory cytokines such as the T H 2-and T H 22-associated mediators IL13 and IL22, respectively, but also of the T H 17-associated [52][53][54] cytokine IL26 (Fig 7, C-E, and E11, C), despite low-to-absent IL17 expression ( Fig E11, G). These cytokines were also found in proliferating (ie, MKI671) ( Fig E11, C) cells of cluster 4 (Fig 7, C-E).…”
Section: Ad Lesions Contain Discrete Populations Of T Cells Nk Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…Cluster 1 showed increased expression of KLF2 (Fig E11, C), a transcription factor involved in T cell homeostasis mediating quiescence and survival, that is present in naive as well as quiescent mature memory T cells, being downregulated upon T-cell receptor-mediated activation. 51 Thus, we conclude that cluster 1 represents quiescent memory T cells, while cluster 0 harbors activated memory T cells with effector functions mediated by active production of proinflammatory cytokines such as the T H 2-and T H 22-associated mediators IL13 and IL22, respectively, but also of the T H 17-associated [52][53][54] cytokine IL26 (Fig 7, C-E, and E11, C), despite low-to-absent IL17 expression ( Fig E11, G). These cytokines were also found in proliferating (ie, MKI671) ( Fig E11, C) cells of cluster 4 (Fig 7, C-E).…”
Section: Ad Lesions Contain Discrete Populations Of T Cells Nk Cellsmentioning
confidence: 85%
“…68 In line, Wolk et al 68 have shown that incubation of T H 17 cells with the IL-4 receptor a ligands IL-4 and IL-13 abrogate the production of IL-17, but not of IL-26, 68 and that IL-26 can promote T H 2-associated cytokine production by KCs in AD. 54 There are several limitations that need to be taken into account. For single-cell transcriptomics, there is currently no standardized bioinformatics approach for analysis due to the novelty of this method.…”
Section: Discussionmentioning
confidence: 99%
“…IL-26 is another cytokine produced by Th17 cells. It was recently reported that IL-26 mRNA expression levels were elevated in AD lesional skin compared with healthy controls and that IL-26-producing cells were increased in AD lesional skin by immunohistochemistry [40]. IL-26 may play an important role for bridging between Th17 and Th2 responses, resulting in the development of AD.…”
Section: Th17-related Cytokine Expression In Admentioning
confidence: 99%
“…Historically, AD is thought to be a Th2 dominated disease. Nonetheless, there is growing evidence that the immunological environment of AD is not solely defined by Th2 cells and related cytokines (IL-4, IL-5, IL-10, IL-13, and IL-31) but also by cytokines linked to other Th cell responses such as IFN-γ (Th1), IL17, or IL-22 (Th17) and IL-33 (an alarmin) (8, 5256). Dupilumab, a mab against IL-4Rα has shown efficacy in a large number of patients and is the first approved biological for AD (57).…”
Section: Atopic Dermatitismentioning
confidence: 99%